ROLE OF THE IMMUNE ORGAN (THYMUS) IN MYSTUS GULIO - B. DEIVASIGAMANI (International Journal of Pharma and Bio Sciences, 2011)
The present work focused on role of the immune organ in the thymus of Mystus gulio. Haemopoietic tissue was found mainly in the spleen, head kidney, thymus and a small amount occurred in the mesonephros. The clearance of the intraperitoneally injected colloidal carbon was carried out. The phagocyte uptake of carbon, after its intraperitoneal injection. It was first detected in the thymus at 30 min after injection.